Education 3640. Problems and issues in special education. No. 12. Newfoundland special education policy draft. - Nesbit, W. C. (Wayne C.), 1943- (Teacher); Karagianis, Leslie D. (Teacher); Memorial University of Newfoundland. Division of Educational Technology (Producer)
Dr. Nesbit interviews Gwenda Jablonski, Assistant Director of Special Education Services with the Government of Newfoundland and Labrador regarding the policy document on special education created by the provincial government. "Dr. W. Nesbitt [sic], Gwenda Jablonski."